Echocardiographic Assessment of the Effect of Mitral Stenosis Severity on Left Ventricular Systolic Function Using Isololumic Myocardial Acceleration (University Heart Journal, 2020)
Background: Isovolumic myocardial acceleration (IVA) is a new tissue Doppler parameter in the assessment of systolic function of both right and left ventricles. It remains unaffected with the changes in pre-and after load with in the physiological range. With the advent of newer parameter like IVA, better assessment are naturally expected. Thus it creates a fertile ground where upon many studies are being done as it chosen here. The aim of study was to assess the effect of MS severety on LV systolic function using IVA.Methods: In this cross sectional study, considering all ethical issues, data were collected from 96 patient (Isolated mitral stenosis and mitral valve area